2021
DOI: 10.12659/msm.932885
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion Regulates Gastrointestinal Motility via HCN1 in Functional Dyspepsia Rats

Abstract: Background Moxibustion therapy has been found to ameliorate clinical symptoms of functional dyspepsia (FD). We aimed to examine the regulatory effect of moxibustion on the gastrointestinal (GI) motility in FD and explore the underlying mechanism based on the hyperpolarization-activated cyclic nucleotide-gated cation channel 1 (HCN1). Material/Methods Moxibustion therapy was used in FD rats induced by using classic tail-pinch and irregular feeding. Weight gain and food i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…S-Moxi, the application of a burning moxa stick above the acupoints from a distance of 2 cm–5 cm, commonly provides constant and stable heat flux at temperatures according to the temperature tolerance of the individual (usually below 44 °C) on the surface of the acupoint for 10∼30 min to exert its therapeutic effect. Many studies have reported that S-Moxi could effectively modulate the intestinal flora [ 7 ], improve gastrointestinal motility [ 8 ], regulate signaling factors associated with cell proliferation and apoptosis, and subsequently promote GU repair [ 9 , 10 ]. GS-Moxi directly places ignited wheat grain-sized moxa cones on the skin of acupoints thus generating an intense burning sensation and mild scald on acupoints in seconds.…”
Section: Introductionmentioning
confidence: 99%
“…S-Moxi, the application of a burning moxa stick above the acupoints from a distance of 2 cm–5 cm, commonly provides constant and stable heat flux at temperatures according to the temperature tolerance of the individual (usually below 44 °C) on the surface of the acupoint for 10∼30 min to exert its therapeutic effect. Many studies have reported that S-Moxi could effectively modulate the intestinal flora [ 7 ], improve gastrointestinal motility [ 8 ], regulate signaling factors associated with cell proliferation and apoptosis, and subsequently promote GU repair [ 9 , 10 ]. GS-Moxi directly places ignited wheat grain-sized moxa cones on the skin of acupoints thus generating an intense burning sensation and mild scald on acupoints in seconds.…”
Section: Introductionmentioning
confidence: 99%